The role of library publishing in making non-traditional research outputs count - Hurrell, Christie; Hall, Robyn (My University, 2023)
Researchers across disciplines are increasingly expected by institutions and funders to engage in knowledge mobilization activities and to openly share a variety of research outputs for the benefit of both researchers and knowledge users in a wide range of contexts. Researchers engaged in knowledge mobilization efforts often create non-traditional outputs that may not easily find a home with established scholarly publishers, who largely remain focused on traditional forms such as journal articles, monographs, and textbooks. As such, researchers may face barriers to openly disseminate, preserve, and track the impact of non-traditional outputs. Library publishing services are well-placed to support researchers producing non-traditional outputs such as reports, policy briefs, data sets, podcasts, digital multimedia projects, and infographics. Research repositories can typically host and preserve a wide variety of content and format types, make these works widely discoverable, and track downloads and other measures of impact. In addition, librarians and library publishing staff have expertise in copyright, research metrics, and digital preservation. By leveraging this infrastructure and expertise, libraries have the opportunity to more broadly disseminate non-traditional outputs, package them in a professional fashion, and assist researchers in more precisely articulating their impact. As such, exploring the ways in which libraries can support this growing area is important as publishing teams expand their scope to include a diverse range of research outputs. It may also help libraries support new research impact evaluation practices and bolster the knowledge mobilization goals of their institutions and researchers. This presentation will outline preliminary research results focused on researcher perspectives and library practices in Canada and the United Kingdom concerning the role and function of non-traditional research outputs. Attendees will be encouraged to consider ways that library publishing services, including but not limited to research repositories, can make these works more discoverable, visible, and measurable.
Presented on May 10, 2023 at the Library Publishing Forum Virtual Conference held online.
Keywords: non-traditional research outputs; library publishing; institutional repositories; knowledge mobilization